2022
DOI: 10.3389/fphys.2021.726719
|View full text |Cite
|
Sign up to set email alerts
|

The Systolic and Diastolic Cardiac Function of Patients With Type 2 Diabetes Mellitus: An Evaluation of Left Ventricular Strain and Torsion Using Conventional and Speckle Tracking Echocardiography

Abstract: Objectives: This study aimed to quantify left ventricular (LV) myocardial strain and torsion in patients with type 2 diabetes mellitus (T2DM) and evaluate their systolic and diastolic function using conventional and speckle tracking echocardiography.Methods: Forty-seven patients with T2DM were divided into a group without microvascular complications (the DM A group) and a group with microvascular complications (the DM B group), while another 27 healthy participants acted as the control group. All the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This model value served as the virtual probability index for the combined utilization of these ve indicators, followed by conducting ROC analysis. (3)The results of the ROC analysis demonstrated that TyG-BMI, METS-IR, IVSD, SBP, LA, and their combined application were all effective in predicting and evaluating cardiac dysfunction in individuals with diabetes. The corresponding ROC-AUC values (95% CI) for these predictors were 0.750 (0.564 ~ 0.934), 0.774 (0.582 ~ 0.944), 0.702 (0.461 ~ 0.948), 0.737 (0.478 ~ 0.983), and 0.726 (0.483 ~ 951) respectively; while the combined application of these ve indices using the Log P model exhibited the highest predictive e ciency with an ROC-AUC value of 0.878 (0.770 ~0.987).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model value served as the virtual probability index for the combined utilization of these ve indicators, followed by conducting ROC analysis. (3)The results of the ROC analysis demonstrated that TyG-BMI, METS-IR, IVSD, SBP, LA, and their combined application were all effective in predicting and evaluating cardiac dysfunction in individuals with diabetes. The corresponding ROC-AUC values (95% CI) for these predictors were 0.750 (0.564 ~ 0.934), 0.774 (0.582 ~ 0.944), 0.702 (0.461 ~ 0.948), 0.737 (0.478 ~ 0.983), and 0.726 (0.483 ~ 951) respectively; while the combined application of these ve indices using the Log P model exhibited the highest predictive e ciency with an ROC-AUC value of 0.878 (0.770 ~0.987).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately half of individuals with diabetes ultimately succumb to cardiovascular events [2]. It has been reported that patients with diabetes may exhibit left ventricular longitudinal myocardial systolic dysfunction, particularly in the presence of early-onset coronary artery disease, valvular disease, and associated cardiovascular risk factors [3][4]. This dysfunction is considered an initial marker of subclinical central impairment in such patients [5], potentially attributed to impaired myocardial energetics metabolism and reduced ventricular systolic strain [6].…”
Section: Introductionmentioning
confidence: 99%
“…The global longitudinal strain (GLS) is a well validated, reproducible tool for the measurement of global left ventricular (LV) systolic function and provides relevant evidence on the diagnostic and prognostic implications ( 10 , 11 ). Reduction in GLS predicts worse cardiovascular outcomes ( 12 , 13 ) and evaluation of such reduction has been applied to the early detection of heart valve diseases, myocardial ischemia, hypertrophic cardiomyopathy, and cardiotoxicity during cancer therapy ( 14 ) as well as in the preclinical detection of cardiac involvement in the systemic, metabolic and endocrine diseases ( 13 , 15 17 ). To date, there have been only a few studies evaluating LV function using STE in patients with active acromegaly and preserved EF ( 8 , 18 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, the potential confounding effects of other coexisting conditions, including but not limited to hyperlipidemia and hypertension, on cardiac function injury have not been adequately addressed. Second, conventional ultrasound parameters have not been comprehensively evaluated in comparative studies (8)(9)(10). Finally, the results of some studies are controversial.…”
Section: Introductionmentioning
confidence: 99%